2018
DOI: 10.1159/000486720
|View full text |Cite
|
Sign up to set email alerts
|

Actionable Locoregional Relapses after Therapy of Localized Esophageal Cancer: Insights from a Large Cohort

Abstract: Objective: The goal of surveillance after therapy of localized esophageal cancer (LEC) is to identify actionable relapses amenable to salvage; however, the current surveillance algorithms are not optimized. We report on a large cohort of LEC patients with actionable locoregional relapses (LRRs). Methods: Between 2000 and 2013, 127 (denominator = 752) patients with actionable LRR were identified. Histologic/cytologic confirmation was the gold standard. All surveillance tools (imaging, endoscopy, fine needle asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Given worsened outcomes in patients with incomplete pathologic responses, there is a pressing need to identify nonresponders early, potentially changing therapies via a personalized approach. The optimal diagnostic method of predicting pCR in esophageal cancer has not been established, although the use of interim fluorine‐18 ( 18 F) fluorodeoxyglucose (FDG) positron emission tomography‐computed tomography is promising 23,24 . Though treatment response is likely dictated by intrinsic tumor biology primarily, little is known about the molecular mechanisms that predict the response of esophageal cancers to CRT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given worsened outcomes in patients with incomplete pathologic responses, there is a pressing need to identify nonresponders early, potentially changing therapies via a personalized approach. The optimal diagnostic method of predicting pCR in esophageal cancer has not been established, although the use of interim fluorine‐18 ( 18 F) fluorodeoxyglucose (FDG) positron emission tomography‐computed tomography is promising 23,24 . Though treatment response is likely dictated by intrinsic tumor biology primarily, little is known about the molecular mechanisms that predict the response of esophageal cancers to CRT.…”
Section: Discussionmentioning
confidence: 99%
“…Current research demonstrates that genetic polymorphisms can predict response to neoadjuvant CRT, particularly mutations among the ERCC1 and XRCC1 genes that play a role in DNA repair 25–28 . While the poor response to initial therapy may suggest tumor resistance to conventional therapies, studies have shown that salvage therapy with radiation or CRT can improve survival in esophageal cancer patients with recurrent disease 23,29,30 . Future studies should investigate if patients with incomplete tumor response would benefit from altering therapy and if these patients can be identified before completion of trimodality therapy to change the approach early and improve outcomes.…”
Section: Discussionmentioning
confidence: 99%